2016
DOI: 10.1139/cgj-2015-0371
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of an extraordinarily mobile rock avalanche in the Northwest Territories, Canada

Abstract: The pre-historic rock avalanche at Avalanche Lake was a spectacularly mobile rock avalanche that resulted in the largest documented runup of any landslide on earth. The runout of the 200 Mm3 event was a complex and three-dimensional process that created three distinct depositional lobes. There is some controversy as to whether the presence of glacial ice played an important role in the dynamics of this event. To investigate this hypothesis an advanced, three-dimensional numerical landslide runout model was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…The best-fit friction angles are 10°and 26°, respectively. The low friction angle in the source zone likely corresponds to extreme polishing of the planar basal rupture surface due to shearing under high normal stress (Cruden & Krahn 1978;Aaron and Hungr, 2016a). The friction angle along the path corresponds closely to that expected for dry fragmented rock (~30°, Hsu (1975)).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The best-fit friction angles are 10°and 26°, respectively. The low friction angle in the source zone likely corresponds to extreme polishing of the planar basal rupture surface due to shearing under high normal stress (Cruden & Krahn 1978;Aaron and Hungr, 2016a). The friction angle along the path corresponds closely to that expected for dry fragmented rock (~30°, Hsu (1975)).…”
Section: Discussionsupporting
confidence: 62%
“…Blasio & Crosta (2015) demonstrated that a steep path combined with isotropic fragmentation can increase centre of mass displacement; however, the effect disappears for slope angles typical of rock avalanche paths. Coe et al (2016) and Aaron & Hungr (2016a) both invoked low basal friction due to entrainment and overriding of saturated soil to explain the dynamics of the West Salt Creek rock avalanche and the Avalanche Lake rock avalanche, respectively. In both cases, this hypothesis was supported by field evidence of entrained path material at the base of the deposit.…”
Section: Introductionmentioning
confidence: 99%
“…Dry rock avalanches usually happen in the mountainous regions. These granular flows are among the most dangerous natural disasters and can cause extensive damages to the engineering structures because of their powerful ability to move freely from their sources and destructive impact energy (Aaron & Hungr, 2016;Robinson et al, 2015). Various mechanisms have been proposed to explain the extremely large flow mobility that particle flows exhibit, such as entrapped air fluidization (Kent, 1966), air cushion theory (Shreve, 1968), dust dispersion fluidization (Hsü, 1975), fluidization caused by acoustic energy (Collins & Melosh, 2003;Melosh, 1979), lubrication by liquefied saturated soil (Hungr & Evans, 2004), size segregation (Iverson et al, 2010;Roche et al, 2011), self-lubrication by molten rock at the base (De Blasio & Elverhøi, 2008;Goren & Aharonov, 2007), and dynamic rock fragmentation (Davies et al, 2010;Langlois et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…During the calibration process, the internal friction angle (φ i ) of the debris flow material was adjusted so that the simulated cable forces and barrier deformations match the field measurements. This parameter was chosen because it dictates the shear strength and energy dissipation of the debris flow as well as the flow-structure interaction (Ng et al, 2018a;Aaron and Hungr, 2016;Mancarella and Hungr, 2010). However, this parameter cannot be readily determined in the field and has to be back-analyzed .…”
Section: Calibration Of the Internal Friction Angle Of Debris Flow Mamentioning
confidence: 99%